2012
DOI: 10.1371/journal.pone.0043891
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Papilloma and Squamous Cell Carcinoma Therapy Utilizing Nanosecond Pulsed Electric Fields (nsPEF)

Abstract: Nanosecond pulsed electric fields (nsPEF) induce apoptotic pathways in human cancer cells. The potential therapeutic effective of nsPEF has been reported in cell lines and in xenograft animal tumor model. The present study investigated the ability of nsPEF to cause cancer cell death in vivo using carcinogen-induced animal tumor model, and the pulse duration of nsPEF was only 7 and 14 nano second (ns). An nsPEF generator as a prototype medical device was used in our studies, which is capable of delivering 7–30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…Cytotoxic efficiency of nsPEF against multiple cancer types has been demonstrated both in vitro [1][7] and in vivo [1], [5], [6], [8][10]. Interestingly, cancer cells reportedly were more vulnerable than matching normal cell lines [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxic efficiency of nsPEF against multiple cancer types has been demonstrated both in vitro [1][7] and in vivo [1], [5], [6], [8][10]. Interestingly, cancer cells reportedly were more vulnerable than matching normal cell lines [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the vast majority of studies into nsPEF-induced cell death focused solely on the apoptotic death pathway. Indeed, various types of cells exposed at lethal nsPEF doses expressed such manifestations of apoptosis as caspase activation, poly-ADP ribose polymerase (PARP) cleavage, cytochrome C release into the cytoplasm, and internucleosomal DNA fragmentation [4], [6], [12], [14]. The only type of necrosis considered in these studies was the so-called “secondary necrosis” (a final cell destruction following the apoptotic process in vitro ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported necrosis due to the colloid-osmotic cell swelling as a predominant mechanism of cell death after exposure to nsEP5610212223. This mechanism could be blocked by isosmotic addition of a nanopore-impermeable solute (such as sucrose) to the growth medium32.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, several groups including ours reported that cells exposed to nsEP swell and may die because of necrosis within the first several hours after the treatment5610212223. Necrosis is caused by the presence of long lived nanopores and colloid-osmotic imbalance which leads to cell swelling and membrane rupture.…”
mentioning
confidence: 81%
See 1 more Smart Citation